The Role of Wattpad Applications in Increasing Reading Interest in the Library Students of The North Sumatera State Islamic University - Anjani, Dwi; Fathurrahman , Muslih (FKIP - Universitas Riau, 2025)
Recent studies on digital literacy highlight a shift in reading interest from print media to interactive digital platforms. However, there is a gap in understanding the impact of applications like Wattpad on the reading interest of students in library science programs. This study aims to determine the role of the Wattpad application in enhancing the reading interest of Library Science students at the State Islamic University of North Sumatra (UINSU), as well as to assess the level of reading interest before and after using Wattpad. A descriptive qualitative approach was employed, with a field study design. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The findings indicate that Wattpad significantly enhances students' reading interest by providing easy access, diverse genres, and interactive features such as comments and voting. Students reported a shift from academic-focused reading to more consistent and enjoyable reading habits. Wattpad serves as an effective digital literacy tool, fostering a sustainable reading culture and supporting the professional development of Library Science students in the digital era.